On the Etymological Awareness of the Traditional Arabic Lexicography: Aethiopica in Lisān al-ʿarab and Tāj al-ʿarūs - Kogan, Leonid (JAOS, 2025)
Arab lexicographers rarely attempted to search for a foreign origin of Arabic words, trying instead to derive them—not very persuasively—from autochthonous Arabic roots. Known exceptions mostly involve Persian, a foreign language par excellence for most Arab philologists. This article explores this phenomenon in a different linguistic domain, viz., loanwords from Classical Ethiopic (Geʿez), the language of the ancient kingdom of Axum (the Horn of Africa). Our harvest, obtained from a systematic perusal of the lexica Lisān al-ʿarab and Tāj al-ʿarūs, is not very rich, but not totally insignificant either; a considerable number of conspicuous examples, often unrecognized in previous scholarship, have been detected, both within the quranic corpus and outside it. Taken together, this evidence provides a unique glimpse into language contacts between Arabia and Ethiopia. It also invites us to reconsider, in a more positive vein, the problem of the etymological awareness of traditional Arab philology.